Assessment of bacterial community diversity in oil palm plantation for isolation and characterisation of ligninolytic bacteria - Abdul Rahman, Nor Hashimah (2016)
The oil palm industry in Malaysia generates huge amount of oil palm biomass every year. The abundant waste of oil palm lignocellulosic biomass is the most favourable renewable source for production of bio-based products. However, the key problem hindering the effective utilisation of oil palm biomass resource is lignin which resulted in low susceptibility of lignocellulose to undergo enzymatic hydrolysis. A biological pre-treatment method using bacteria was chosen in this study to remove lignin. Ligninolytic bacteria have wider tolerance of temperature, pH and oxygen limitations compared to fungi. It is also easier to handle for large-scale growth production and genetic manipulation. Assessment of bacterial community profile in oil palm plantation soils was conducted by using 16S rRNA gene clone library approach and biodiversity index analysis of operational taxonomic units (OTUs). 16S rRNA gene clone library analysis retrieved 351 clones from three selected samples of oil palm plantation soils. The most dominant groups were Proteobacteria followed by Acidobacteria and Bacteroidetes. Phylogenetic analysis of dominant bacterial clone sequences revealed many potential lignin degrading bacteria from genus Stenotrophomonas, Acinetobacter, Flavobacterium and Sphingomonas. The Shannon’s diversity index (H) shows high value from 3.24 to 3.42 indicating the high level of species richness in the soil samples. Isolation and identification of ligninolytic bacteria were executed from oil palm plantation soils samples. Bacterial isolates were screened using minimum salt media (MSM) with kraft lignin (KL) as sole carbon source and methylene blue as ligninolytic dye indicator. Furthermore, the ability of strains to grow on high tolerance concentrations of KL was observed. Three bacterial isolates; SHC1, SHC2 and SHC3 were selected for further study. The identification and characterisation of selected strains were conducted using 16S rRNA gene sequence analysis and biochemical test by Biolog. The isolate SHC1 was identified as Bacillus cereus and SHC2 strain as Ochrobactrum ciceri with 99% sequence similarity, respectively. Meanwhile, strain SHC3 was identified as Leucobacter komagatae at 100% identity homology.The ability of selected isolates to degrade lignin was examined through the production of ligninolytic enzymes such as manganese peroxidase (MnP), lignin peroxidase (LiP) and laccase. The submerged fermentation experiments were conducted for 7 days using KL and oil palm empty fruit bunch (OPEFB) as substrate. B. cereus SHC1 was found to be the highest MnP and LiP enzyme producers among other selected bacteria in this study. The maximum MnP and LiP enzyme activities production by B. cereus SHC1 was at 2313.4 U/L (third day) and 209.30 U/L (fifth day), respectively. The influences of culture conditions such as pH and temperature conditions were carried out to maximise the production of ligninolytic enzymes by B. cereus SHC1. Therefore, the optimum pH and temperature of B. cereus SHC1 were pH 8 and 30°C, respectively.Thus, the isolated ligninolytic bacteria from oil palm plantation soils have proven to produce high ligninolytic enzymes from oil palm lignin residue in OPEFB. This isolated ligninolytic bacteria may have specific advantages for the lignin degradation in oil palm biomass. Further studies on the mechanism of lignin degradation from this isolated ligninolytic bacteria could provide an effective ways for utilisation of oil palm biomass into bio-based products.